PERAWATAN DIRI IBU NIFAS SEBAGAI UPAYA MENCEGAH INFEKSI NIFAS - ., Mardiatun (Jurnal Health and Sport, 2013)
Postpartum self-care is a follow-up for women after childbirth, self-care during childbirth is necessary because a lot of women will have physical and psychological changes experience. Postpartum care is a critical point but often is ignored component of postpartum self care. In developing countries, about 70% did not receive postpartum care, postpartum care most acceptable when there is a risk of maternal death in childbirth, postpartum maternal death is 50% - 71% occur in the postpartum period. The most common cause of maternal death is hemorrhage, second direct cause is an infection, is responsible for most deaths late postpartum. Morbidity in the first week postpartum is usually caused by endrometritis, mastitis, infection of the episiotomy or laceration, urinerius tract infections, and other diseases. Postpartum self-care can be done in a way: Meets Nutrition, early mobilization, meet Urine elimination, maintain personal hygiene, breast treatment, and care of the perineum. Postpartum self-care is not only important to reduce maternal mortality and morbidity but also to strengthen and improve healthy behaviors and to restore public health puerperal women during treatment.